2019
DOI: 10.1002/dac.4183
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Zadoff‐Chu and multilateral piecewise exponential companding transform–based PAPR reduction technique in OFDM systems

Abstract: SummaryThe orthogonal frequency‐division multiplexing (OFDM) is a multicarrier modulation system that is used to transmit the large volume of data to the receiver. Reducing the peak‐to‐average power ratio (PAPR) in OFDM system is one of the demanding and crucial task in recent days. For this reason, various precoding and companding mechanisms are developed in the traditional works, but it remains with the limitations of increased complexity, reduced performance, and nonlinear distortion. The reduction of PAPR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The authors in [ 34 ] showed that Zadoff–Chu Transform hybridized with -law (ZCT- ) is better than WHT- from PAPR reduction point of view. The authors in [ 35 ] hybridized ZCT with the Piecewise Exponential Companding technique. However, the solution is impractical because it uses inflection point and side information data as PLC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors in [ 34 ] showed that Zadoff–Chu Transform hybridized with -law (ZCT- ) is better than WHT- from PAPR reduction point of view. The authors in [ 35 ] hybridized ZCT with the Piecewise Exponential Companding technique. However, the solution is impractical because it uses inflection point and side information data as PLC.…”
Section: Introductionmentioning
confidence: 99%
“… Many precoding-companding techniques [ 26 , 29 , 31 , 36 , 37 ], are not compared with any previous works. HPA was neglected in the models [ 22 , 26 , 27 , 28 , 30 , 31 , 33 , 34 , 35 , 36 , 37 ], although HPA is the source of nonlinear distortion. The authors in [ 22 , 26 , 28 , 30 , 31 , 34 , 36 , 37 ] have not considered Rayleigh channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Thus, the PAPR should be reduced to eliminate the nonlinear distortion and improve the performance of bit error rate (BER). 3,4 Many PAPR reduction approaches have been reported in the previous studies, such as clipping and filtering, 5 nonlinear companding, 6 coding, 7 tone reservation (TR), 8 ton injection (TI), 9 precoding-based methods, 10,11 partial transmit sequence (PTS), 12,13 and selective mapping (SLM). 14 The extensive research on PAPR reduction methods is also surveyed.…”
Section: Introductionmentioning
confidence: 99%
“…5 In the companding approach, the OFDM signal is applied to a companding function at the transmitter side, and a decompander is applied to recover the original signal at the receiver end. 6 In the coding technique, a specific codeword is used before modulation to minimize the PAPR. 7 In TR and TI techniques, a subset of tones is reserved by transmitter and receiver to reduce the PAPR.…”
Section: Introductionmentioning
confidence: 99%